2010
DOI: 10.1016/j.cbi.2009.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induction by (+)-cordiaquinone J triggers both mitochondria-dependent apoptosis and necrosis in leukemia cells

Abstract: (+)-Cordiaquinone J is a 1,4-naphthoquinone isolated from the roots of Cordia leucocephala that has antifungal and larvicidal effects. However, the cytotoxic effects of (+)-cordiaquinone J have never being explored. In the present study, the effect of (+)-cordiaquinone J on tumor cells viability was investigated, showing IC(50) values in the range of 2.7-6.6muM in HL-60 and SF-295 cells, respectively. Studies performed in HL-60 leukemia cells indicated that (+)-cordiaquinone J (1.5 and 3.0muM) reduces cell via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
1
15
0
1
Order By: Relevance
“…[61,67,70] Cordiaquinone J was found to be active against HL-60 and SF-295 cells with 2.7 lm and 6.6 lm IC 50 value, respectively, when screened for cytotoxicity study. [71] Four meroterpenoid benzoquinones were found to be present in two Cordia species, that is (1aS*,1bS*, 7aS*,8aS*)-4,5-dimethoxy-1a,7a-dimethyl-1,1a,1b,2,7,7a,8, 8a-octahydrocyclopropa [3,4]cyclopenta[1,2-b]naphthalene-3,6-dione (31) and microphyllaquinone (34) in C. globosa, and globiferin (32) and globiferane (33) in C. globifera. [72,73] Compounds 31 and 34 were investigated for cytotoxicity study which showed a significant effect with IC 50 value of 1.2-5 lg/ml [72] (Table 2.1.2).…”
Section: Meroterpenoid Quinonesmentioning
confidence: 99%
See 1 more Smart Citation
“…[61,67,70] Cordiaquinone J was found to be active against HL-60 and SF-295 cells with 2.7 lm and 6.6 lm IC 50 value, respectively, when screened for cytotoxicity study. [71] Four meroterpenoid benzoquinones were found to be present in two Cordia species, that is (1aS*,1bS*, 7aS*,8aS*)-4,5-dimethoxy-1a,7a-dimethyl-1,1a,1b,2,7,7a,8, 8a-octahydrocyclopropa [3,4]cyclopenta[1,2-b]naphthalene-3,6-dione (31) and microphyllaquinone (34) in C. globosa, and globiferin (32) and globiferane (33) in C. globifera. [72,73] Compounds 31 and 34 were investigated for cytotoxicity study which showed a significant effect with IC 50 value of 1.2-5 lg/ml [72] (Table 2.1.2).…”
Section: Meroterpenoid Quinonesmentioning
confidence: 99%
“…Antimicrobial Showed significant activity against S. aureus, S. epidermidis, Bacillus subtilis, P. aeruginosa, P. aeruginosa, E. coli, Shigella flexineri, C. albicans, C. tropicalis, C. tropicalis, C. krusei, C. krusei, C. guilliermondii and C. guilliermondii [92] 8,8 0 -dimethyl-4,5-dimethoxy-3 0 ,4 0 -methylenodioxy-7-oxo-2,7 0 cyclolignan Antimicrobial Showed significant activity against S. aureus, S. aureus, S. epidermidis, Bacillus subtilis, P. aeruginosa, P. aeruginosa, E. coli, Shigella flexineri, C. albicans, C. tropicalis, C. tropicalis, C. krusei, C. krusei, C. guilliermondii and C. guilliermondii [92] Cordiarimides A and B Antioxidant Showed significant antioxidant in xanthine/xanthine oxidase (XXO) assay and in HL-60 human promyelocytic leukaemia cells [37] Globiferin Antimycobacterial Active against Mycobacterium tuberculosis H 37 Ra with MIC value of 6.2 lg/ml [73] Cordiachrome C Antimycobacterial Active against Mycobacterium tuberculosis H 37 Ra with MIC value of 1.5 lg/ml [73] 1AS*,1bS*,7aS*,8aS*)- [72] Trypanocidal Active against epimastigote forms of Trypanosoma cruzi [46] Cordigone, cordigol, benzofuran III, benzofuran IV Antifungal Active against Cladosporium cucumerinum [103] (+)-Cordiaquinone J Cytotoxic Demonstrated cytotoxic effect with IC 50 value from 2.7 to 6.6 lM in the cell lines HL-60 and SF-295, respectively [71] Cordiaquinone E Antifungal and larvicidal Active against Cladosporium cucumerinum (MIC 3 lg/ml), Candida albicans (MIC 6 lg/ml) and against the larvae of Aedes aegypti (MIC 12.5 lg/ml) [67] Cordiaquinone G Antifungal Active against Cladosporium cucumerinum (MIC 3 lg/ml), Candida albicans (MIC 6 lg/ml) [67] Cordiaquinone F Antifungal and larvicidal Active against Cladosporium cucumerinum (MIC 1.5 lg/ml), Candida albicans (MIC 6 lg/ml) and against the larvae of Aedes aegypti (MIC 25 lg/ml) [67] jararacussu and phospholipase A2 homologs, that is bothropstoxins I and II, in mice. The extract and rosmarinic acid also showed significant antimyotoxic activity against snake venom and isolated toxins in mice.…”
Section: Antimyotoxic and Antivenom Activitymentioning
confidence: 99%
“…Although their precise mechanism of action is not yet fully understood, it is suggested that their major target is DNA. While some interact with DNA by alkylation or intercalation, others induce double strand DNA breaks and both DNA topoisomerase I and II mediated DNA cleavage (Asche 2005;Cai et al 2007Cai et al , 2008Marinho-Filho et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To assay internucleosomal DNA fragmentation, the cells were incubated at 37 °C for 30 min in the dark in a lysis solution containing 0.1% citrate, 0.1% Triton X-100 and 50 µg mL -1 PI, and the percentage of degraded DNA was determined according to the number of cells displaying subdiploid (sub-G o /G 1 ) DNA in relation to the total number of cells examined. 31 Transmembrane mitochondrial potential (DYm) was evaluated using Rho-123 incorporation according to the method described by Marinho-Filho et al 32 Rho-123 is a cell-permeable, cationic, fluorescent dye that is readily sequestered by active mitochondria without inducing cytotoxic effects. Fluorescence was measured, and the percentage of mitochondrial depolarization was determined.…”
Section: Analysis Of Mechanisms Involved In Cytotoxicitymentioning
confidence: 99%